2019
DOI: 10.1111/tpj.14223
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing microRNA167A expression in seed decreases the α‐linolenic acid content and increases seed size in Camelina sativa

Abstract: These authors contributed equally to this work. SUMMARYDespite well established roles of microRNAs in plant development, few aspects have been addressed to understand their effects in seeds especially on lipid metabolism. In this study, we showed that overexpressing microRNA167A (miR167OE) in camelina (Camelina sativa) under a seed-specific promoter changed fatty acid composition and increased seed size. Specifically, the miR167OE seeds had a lower a-linolenic acid with a concomitantly higher linoleic acid con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 108 publications
1
32
0
Order By: Relevance
“…Indeed, recent studies have shown that some auxin signaling components or genes regulated by the auxin signaling pathway can alter seed size and/or seed weight. For instance, ARF6 and ARF8, which are partially controlled by microR167, appear to be required for seed size in Camelina [98]. Big Grain 1 (BG1), which is a plasma membrane-associated protein involved in auxin transport and the auxin response, has the potential to improve both grain size and weight in rice [99].…”
Section: Auxin Is a Main Factor Influencing Seed Size And Seed Weightmentioning
confidence: 99%
“…Indeed, recent studies have shown that some auxin signaling components or genes regulated by the auxin signaling pathway can alter seed size and/or seed weight. For instance, ARF6 and ARF8, which are partially controlled by microR167, appear to be required for seed size in Camelina [98]. Big Grain 1 (BG1), which is a plasma membrane-associated protein involved in auxin transport and the auxin response, has the potential to improve both grain size and weight in rice [99].…”
Section: Auxin Is a Main Factor Influencing Seed Size And Seed Weightmentioning
confidence: 99%
“…Numerous studies have focused on camelina seed yields and oil quality [8,9]. For example, the over-expression of micro-RNA167A in C. sativa seeds reduced the α-linolenic acid content and increased the seed size [10]. The expression of diacylglycerol acyltransferase 1 and glycerol-3phosphate dehydrogenase increased the seed oil yields in C. sativa [11].…”
Section: Introductionmentioning
confidence: 99%
“…MiR167 targeted the transcription factor ARF genes had been reported to be conserved among other plant species, including rice (Liu et al, 2012a), soybean (Wang et al, 2015), tomato (Liu et al, 2014), Ipomoea nil (Glazinska et al, 2014), Camelina sativa (Na et al, 2019) and so on. A total of 25 putative OsARFs have been identified in of rice (Guilfoyle and Hagen, 2007;Li et al, 2016;Wang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%